Deal! the bottom line of business English / : course book. - D'Haens, Adriaan, 1984-; Du Pont, Olaf, 1977-; Jacobs, Geert, 1966- (Leuven : Acco, 2012)
Deal! is a comprehensive pre-work Business English course for speakers of Dutch. It includes a reference book, featuring vocabulary, skills and grammar, as well as a course book, focusing on oral and written communication. This course book includes a "business boot camp" introducing learners to what's in it for Me, My Business and My World as well as 10 free-standing chapters that look at a wide range of business-related topics from corporate culture, mergers and takeovers to marketing, globalization and innovation. It features dozens of exciting, authentic and up-to-date cases on Willy Wonka and Karl Marx, Earth Hour, big business and the Fukushima earthquake, women and Mad Men, the waterless washing machine, Ben & Jerry's and Unilever, and fake Van Goghs made in China. It draws on video materials from international media and new texts from newspapers and on-line resources.
Business boot camp - 1. on your markets, get set, go! - 2. work it! - 3. the corporate culture clash - 4. in the marketing mix - 5. going global - 6. of nuts and bolts - 7. breaking the mould - 8. dollars in and out - 9. put your money where your mouth is - 10. love is in the air - multimedia - sources
Handboek bij cursus 'Economisch Engels' (Geert Jacobs)
Keywords: Zakelijk Engels